Utilização de humina como um material alternativo na adsorção/dessorção de corantes reativos - Jesus, Amanda Maria Dantas de (2010)
Environmental problems have become increasingly acute and frequent in recent decades, mainly due to unrestrained population growth and increased industrial activity. The textile industry merits especial attention in this context, since large volumes of water are used in finishing processes, which results in substantial quantities of liquid effluent. The objective of this work was to determine the optimum conditions for adsorption/desorption of reactive dyes, employing humin in batch experiments and with fixed bed columns where the humin was immobilized on silicate. Immobilization was confirmed by Fourier transform infrared analysis. Adsorption isotherms were constructed, and the kinetic data fitted to literature models. Multiple adsorption/desorption cycles were investigated using the fixed bed column. Results of the batch experiments showed that adsorption of Reactive Red 120 (RR 120) and Reactive Orange 16 (RO 16) by humin was most effective at pH 1.0, while optimum adsorption of Reactive Blue 2 (RB 2) was obtained at pH 2.0. Adsorption equilibria were rapidly achieved for all initial dye concentrations tested. Temperature measurements indicated that all of the processes were exothermic and could be described using a pseudo-second order kinetic model. The Freundlich isotherm provided the best fit for RO 16, while the Langmuir isotherm best described the adsorption of RR 120 and RB 2. In column experiments, adsorption efficiencies of 96.2 %, 62.1 % and 44.6 % were obtained for RR 120, RO 16 and RB 2, respectively, while the corresponding desorption efficiencies for these dyes were 81.4 %, 51.3 % and 23.7 %, respectively. Reductions in retention efficiency of 16 % (RO 16), 21 % (RR 120) and 26 % (RB 2) were observed between the first and second cycles. Reductions between the second and third cycles were of 7 %, 1 % and 1 %, respectively, indicating that the column could be used in further cycles. Overall, the biosorbent showed excellent performance in removal of reactive dyes, with the additional advantage that it could be regenerated and reused.